2015
DOI: 10.1097/ajp.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Hydrocodone Therapy Based on Phenotype, Pharmacogenetics, and Pharmacokinetic Dosing

Abstract: Our results demonstrate that pharmacogenetics afford clinicians an opportunity to individualize HC dosing, while adding enhanced opportunity to account for its conversion to HM in the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The model also showed that about 40% of a codeine dose was converted to morphine in EM subjects, and about 51% was converted to morphine in ultrarapid-metabolizers… Our study suggests that pharmacogenetics for personalized dosing might be most effectively advanced by studying the interplay between pharmacogenetics, population pharmacokinetics, and clinical pharmacokinetics." 197 Individualized Hydrocodone Therapy Based on Phenotype, Pharmacogenetics, and Pharmacokinetic Dosing http://www.ncbi.nlm.nih.gov/pubmed/?25621429 198 "Our results demonstrate that pharmacogenetics afford clinicians an opportunity to individualize [hydrocodone] HC dosing, while adding enhanced opportunity to account for its conversion to HM in the body." 198 Gene Tested: Cytochrome P450 3A4/5: (CYP3A4/5) There is a large amount of variability in psychotropic drug response and variations in CYP450 genes, including CYP3A4/5, may impact this variability.…”
Section: Impact Of Multiple Inhibitors or Substrates Of Cytochrome P4mentioning
confidence: 82%
See 1 more Smart Citation
“…The model also showed that about 40% of a codeine dose was converted to morphine in EM subjects, and about 51% was converted to morphine in ultrarapid-metabolizers… Our study suggests that pharmacogenetics for personalized dosing might be most effectively advanced by studying the interplay between pharmacogenetics, population pharmacokinetics, and clinical pharmacokinetics." 197 Individualized Hydrocodone Therapy Based on Phenotype, Pharmacogenetics, and Pharmacokinetic Dosing http://www.ncbi.nlm.nih.gov/pubmed/?25621429 198 "Our results demonstrate that pharmacogenetics afford clinicians an opportunity to individualize [hydrocodone] HC dosing, while adding enhanced opportunity to account for its conversion to HM in the body." 198 Gene Tested: Cytochrome P450 3A4/5: (CYP3A4/5) There is a large amount of variability in psychotropic drug response and variations in CYP450 genes, including CYP3A4/5, may impact this variability.…”
Section: Impact Of Multiple Inhibitors or Substrates Of Cytochrome P4mentioning
confidence: 82%
“…197 Individualized Hydrocodone Therapy Based on Phenotype, Pharmacogenetics, and Pharmacokinetic Dosing http://www.ncbi.nlm.nih.gov/pubmed/?25621429 198 "Our results demonstrate that pharmacogenetics afford clinicians an opportunity to individualize [hydrocodone] HC dosing, while adding enhanced opportunity to account for its conversion to HM in the body." 198 Gene Tested: Cytochrome P450 3A4/5: (CYP3A4/5) There is a large amount of variability in psychotropic drug response and variations in CYP450 genes, including CYP3A4/5, may impact this variability. There are several articles which review the relevant clinical implications of altered CYP3A4/5 metabolism.…”
Section: Impact Of Multiple Inhibitors or Substrates Of Cytochrome P4mentioning
confidence: 82%
“…(14) Further, pharmacogenetics data suggest that opioids including hydrocodone, oxycodone, and codeine may be ineffective in up to 10% of the Caucasian population. (30,31,32) As a result, best practice recommendations note that opioid analgesics should be reserved for the minority of situations in which optimal doses of NSAIDs and/or acetaminophen/aspirin provide insufficient pain management. (14,29)…”
Section: Discussionmentioning
confidence: 99%
“…This patient's genotype predicts a CYP2D6 intermediate metabolizer phenotype which has been shown to occur iñ 13% of African Americans; thus, pharmacogenomic testing would have predicted substantially lower active metabolites of tramadol and hydrocodone and consequently, inefficacy (Swen et al, 2011;Crews et al, 2014;Linares et al, 2015). In addition, she was also taking fluoxetine to treat her depression, a common co-morbidity with chronic pain, which would have reduced further her endogenous CYP2D6 activity.…”
Section: Discussionmentioning
confidence: 98%
“…The patient's family history was significant, as her mother progressed to end-stage renal disease. Her CYP2D6 genotype was *5/*17, a gene deletion which is reported to occur in 2-11% of people and is consistent with intermediate metabolism making tramadol and hydrocodone less effective (Swen et al, 2011;Crews et al, 2014;Linares et al, 2015). A retrospective look at the urine drug screen noted the absence of any hydromorphone, the more active metabolite of hydrocodone, even though hydrocodone was detected (233 ng/ml).…”
Section: Case Presentationmentioning
confidence: 98%